2013
DOI: 10.4150/kpmi.2013.20.6.405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Passivation on the Sintering Behavior of Submicron Nickel Powder Compacts for MLCC Application

Abstract: During sintering of Ni-electrode multi-layer ceramic capacitors (MLCCs), the Ni electrode often becomes discontinuous because of its lower sintering temperature relative to that of BaTiO 3. In an attempt to retard the sintering of Ni, we introduced passivation of the Ni powder. To find the optimal passivation conditions, a thermogravimetric analysis (TGA) was conducted in air. After passivation at 250 o C for 11 h in air, a nickel oxide shell with a thickness of 4-5 nm was formed on nickel nanoparticles of 180… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…So obviously there was a need to assess the conductivity of Ni foils after a real sintering process. Based on the other studies on sintering Ni particles [47][48][49][50], the heating schedule of 1020 °C for 4 min was selected, and then it was confirmed that Ni particles could be successfully sintered with it. This heat treatment would be used as a criterion to evaluate the merit of the ALD coatings to preserve Ni conductivity during the sintering of Ni particles.…”
Section: Methodsmentioning
confidence: 99%
“…So obviously there was a need to assess the conductivity of Ni foils after a real sintering process. Based on the other studies on sintering Ni particles [47][48][49][50], the heating schedule of 1020 °C for 4 min was selected, and then it was confirmed that Ni particles could be successfully sintered with it. This heat treatment would be used as a criterion to evaluate the merit of the ALD coatings to preserve Ni conductivity during the sintering of Ni particles.…”
Section: Methodsmentioning
confidence: 99%
“…The nickel and BaTiO 3 multilayers, and especially the Ni electrode itself, have been studied in detail. As mentioned above, one common practice is to reduce the amount of oxygen vacancies by post-reoxidation process.…”
Section: Introductionmentioning
confidence: 99%